Extreme‐Value Statistics Reveal Rare Failure‐Critical Defects in Additive Manufacturing1 . Issue 8 (21st April 2017) - Boyce, Brad L.; Salzbrenner, Bradley C.; Rodelas, Jeffrey M.; Swiler, Laura P.; Madison, Jonathan D.; Jared, Bradley H.; Shen, Yu‐Lin
Abstract : Additive manufacturing enables the rapid, cost effective production of customized structural components. To fully capitalize on the agility of additive manufacturing, it is necessary to develop complementary high‐throughput materials evaluation techniques. In this study, over 1000 nominally identical tensile tests are used to explore the effect of process variability on the mechanical property distributions of a precipitation hardened stainless steel produced by a laser powder bed fusion process, also known as direct metal laser sintering or selective laser melting. With this large dataset, rare defects are revealed that affect only ≈2% of the population, stemming from a single build lot of material. The rare defects cause a substantial loss in ductility and are associated with an interconnected network of porosity. The adoption of streamlined test methods will be paramount to diagnosing and mitigating such dangerous anomalies in future structural components. Abstract : Arrays of tensile bars printed by laser powder bed fusion (additive manufacturing) are tested with a high‐throughput mechanical test method. The resulting property distributions reveal within‐ and between‐build variability as well as anomalous behavior associated with rare, failure‐critical defects.